Systemic Lupus Erithematosus (SLE) With Tuberculosis Lymphadenitis: A Case Report - Wahyudi, Slamet; Awalia, Awalia (Journal of Neonatal Surgery, 2025)
Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease characterized by multisystem involvement and a heightened risk of infection due to immune dysregulation and immunosuppressive therapy. Tuberculosis (TB), particularly extrapulmonary forms like lymphadenitis, poses a significant threat to SLE patients, especially in TB-endemic regions. Case Presentation: We report a case of a 22-year-old woman with a known history of SLE who presented with fever, persistent cough, and a progressively enlarging left cervical mass. The patient had been on immunosuppressive therapy, including methylprednisolone and cyclosporine. Physical examination and imaging revealed cervical lymphadenopathy, and fine needle aspiration biopsy (FNAB) confirmed TB lymphadenitis through the presence of acid-fast bacilli. GeneXpert testing of sputum further identified rifampicin-sensitive mycobacterium tuberculosis. The patient was treated with standard anti-tubercular therapy (2HRZE/4HR) while SLE management was continued with low-dose corticosteroids, folic acid, and calcium supplementation, guided by a SLEDAI-2K score of 0, indicating no active disease. Outcome: Over a 6-month treatment period, the patient showed clinical improvement with resolution of the cervical mass, disappearance of respiratory symptoms, and weight gain. Laboratory parameters also improved, and no SLE flare was noted throughout TB treatment. Conclusion: This case highlights the importance of early recognition and appropriate management of TB lymphadenitis in immunocompromised patients with SLE. FNAB remains a key diagnostic tool, and a multidisciplinary approach is critical to balancing anti-tuberculous therapy and autoimmune disease management without exacerbating either condition